2015
DOI: 10.17221/74/2013-rae
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research on phytomass suitable for production of biogas

Abstract: Pastorek M., Kára J., Pastorek Z. (2015): Experimental research on phytomass suitable for production of biogas. Res. Agr. Eng., 61: 129-133.The structure of the dry material plant is made up of a cell tissues system. The walls of the cells are formed by cellulose and lignin, ingredients difficult to biodegrade. Therefore, the aim of the breeders performed a variety of energy plants, providing a high yield of dry matter in the green state. This applies particularly to herbs, grown on agricultural and arable lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…2; ETI 8040, Moisture tester; ETI, West Sussex, United Kingdom). Net calorific value of the burned fuel wood was determined according to Pastorek et al (2004): with other alternatives of fuel wood burning (with the same input value of the housing units). For an objective assessment of the thermal potential of fuel wood, other methods of heating were compared, which are also commonly used as a source of heat in the area of our study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2; ETI 8040, Moisture tester; ETI, West Sussex, United Kingdom). Net calorific value of the burned fuel wood was determined according to Pastorek et al (2004): with other alternatives of fuel wood burning (with the same input value of the housing units). For an objective assessment of the thermal potential of fuel wood, other methods of heating were compared, which are also commonly used as a source of heat in the area of our study.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, when calculating the net calorific value of fuel wood it is needed to know net calorific value of dry matter, which means the fuel wood combustive efficiency of fuel wood at 0% of absolute moisture (Ampatzi et al 2013). Since this value is not commonly recognised in practise it is recommended to use calculation of the theoretical value, following Pastorek et al (2004), H s = 18.5 MJ/kg.…”
Section: Properties Of Burned Fuel Woodmentioning
confidence: 99%
See 1 more Smart Citation
“…The retrieved studies from the Czech Republic registered two different valorizations of AWB alternatives, which were the transformation for biogas and bioenergy production as an additional source of energy; it was also identified that the produced digestate after processing the agricultural wastes has a major use as organic fertilizer, this contributes to improving the organic fertilizer management in agriculture or in the municipal sphere (Kodymová, 2014;Pastorek et al, 2013). Although biogas production is the main focus of 45% of the studies (Figure 5), which included the use of pellets made from agricultural waste (wheat and rice straw and hay), the syngas produced after the gasification process could be used for liquid fuel synthesis (Najser et al, 2014).…”
Section: Main Alternatives For the Valorization Of Awb -Czech Republicmentioning
confidence: 99%
“…Especially for the production of biofuels and bioenergy, two of the main types of bio-based products obtained from the analysis (García- Maraver et al, 2012;. In the case of the Czech Republic, the production of these bio-based products from cereal crop straw (Havlíčková et al, 2009;Havlíčková et al, 2010;Pastorek et al, 2013;Vávrová et al, 2014) has been studied. Other studies confirm that this type of AWB, due to its high concentration of lignocellulose (80%), has been the most widely used for producing bioenergy and biofuels (Duque-Acevedo et al, 2020b.…”
Section: Czech Republicmentioning
confidence: 99%